ANALISIS PERSEPSI PUBLIK DI MEDIA SOSIAL TERHADAP PRODUK HALAL DI INDONESIA MENGGUNAKAN TEXT MINING - Maarif, Muhammad Rifqi; Salim, D Jayus Nor (INDONESIAN JOURNAL ON DATA SCIENCE, 2024)
The assurance of the halal status of a product is crucial for Muslim consumers, especially in Indonesia, the country with the largest Muslim population in the world. The government, through the Ministry of Religious Affairs, has implemented halal certification to ensure the validity of products. However, the implementation of the halal assurance system remains controversial, with some viewing it as an effort for government profit, particularly by the Ministry of Religious Affairs through the Indonesian Council of Ulama (MUI). Negative sentiments from opposing groups have the potential to escalate and influence other individuals or communities if not properly addressed. One preventive measure is to promote education and awareness of halal products through digital media, especially social media. Given the widespread use of social media, particularly among millennials, it can serve as an effective and cost-efficient platform for education and promotion. Educational efforts via social media require specific strategies to ensure the optimal dissemination of information as intended. Understanding the patterns and characteristics of content as well as the socio-cultural context of social media users is essential. This understanding can be achieved through a comprehensive analysis of the diverse and abundant user-generated content on social media platforms. Therefore, this study proposes a text mining-based method to develop a framework for understanding the characteristics and dynamics of public discourse on halal products on social media.